Keanekaragaman Jenis Ikan Karang di Fish Shelter Perairan Rebo Kecamatan Sungailiat Kabupaten Bangka - Pratama, Sandy Agustia Pratama; Umroh; Utami, Eva (Jurnal Ilmu Kelautan Lesser Sunda, 2023)
Tin mining activities carried out in Bangka Island waters have a negative impact on the coral reef ecosystem. Overcoming this problem requires efforts to rehabilitate coral reef ecosystems, such as sinking fish shelters in these waters, which can provide new habitats for reef fish. The purpose of this study was to determine the type of reef fish diversity in fish shelters in 3 different years of sinking. This research was conducted in May 2022 in Rebo Waters, using the visual census method. The results stated that the presence of reef fish species found at the three stations was 55 species from 22 families. The diversity index value at station 1 was 2.04, station 2 was 1.36and station 3 was 1.63. The uniformity index value at station 1 was 0.55 station 2 was 0.41 and station 3 was 0.43. The dominance index value at station 1 is 0.24, station 2 is 0.37 and station 3 is 0.32. The biomass calculation value at station 1 was 0.23, station 2 was 0.36 and station 3 was 0.33.